Dinamika Perkembangan Ilmu Komunikasi dari Masa ke Masa - Neyza Nur Eisyah Agisti; Revalya Rahma Putri; Alvin Faiz Adzikra; Rakha Razeva Abhipraya (PT. Hasba Edukasi Mandiri, 2025)
This study aims to describe the dynamics of the development of communication science from the pre-modern era to the digital era. In the process, this study uses a descriptive qualitative approach with a library study method, which focuses on the study of scientific and historical literature. The results of the study show that communication has undergone significant transformation along with the development of technology, social change, and the development of science. Starting from symbolic and oral communication in the pre-modern era, then developing into written and printed communication in the classical to early modern eras, then experiencing strengthening as a scientific discipline in the 20th century, and finally entering the phase of digital communication which is interactive and global. This study also found that each period has unique characteristics that influence the way humans convey messages, build relationships, and shape meaning. This finding is important for understanding how communication is not only a technical activity, but also a socio-cultural process that continues to evolve. By understanding the historical trajectory of communication, it is hoped that critical awareness will emerge regarding the role of communication in shaping civilization.